2017
DOI: 10.2147/ijn.s124770
|View full text |Cite
|
Sign up to set email alerts
|

Targeted multidrug delivery system to overcome chemoresistance in breast cancer

Abstract: Chemotherapy has been widely used in breast cancer patients to reduce tumor size. However, most anticancer agents cannot differentiate between cancerous and normal cells, resulting in severe systemic toxicity. In addition, acquired drug resistance during the chemotherapy treatment further decreases treatment efficacy. With the proper treatment strategy, nanodrug carriers, such as liposomes/immunoliposomes, may be able to reduce undesired side effects of chemotherapy, to overcome the acquired multidrug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 44 publications
(51 reference statements)
0
29
0
Order By: Relevance
“…Anthracyclines are still the most widely used chemotherapeutic agents given as either adjuvant or neoadjuvant therapy [11,12]. Considering that approximately 30% of the early stage breast cancers progress to the metastatic stage, and the fact that the response rate to anthracycline or taxane-based chemotherapy ranges from 30 to 70%, predictors of treatment efficacy to the various chemotherapeutic agents would have significant clinical importance [1,3,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines are still the most widely used chemotherapeutic agents given as either adjuvant or neoadjuvant therapy [11,12]. Considering that approximately 30% of the early stage breast cancers progress to the metastatic stage, and the fact that the response rate to anthracycline or taxane-based chemotherapy ranges from 30 to 70%, predictors of treatment efficacy to the various chemotherapeutic agents would have significant clinical importance [1,3,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 summarizes a number of recent studies on HER2-targeted nanomedicine. [55][56][57][58][59] Although HER2 antibody is a targeting moiety commonly used for HER2+ cancer, other HER2 targeting ligands have also been studied. For instance, Ding et al used trastuzumab-mimetic peptide with promising results, and suggested that this may reduce the immunogenicity, production costs and technical efforts associated with the antibody.…”
Section: Latest Trend For the Development Of Nanomedicine-based Breasmentioning
confidence: 99%
“…HER2 antibody was used in a recent study as a targeting ligand in PEGylated immunoliposomes loaded with DOX. The formulation was tested for combination therapy in association with liposomal bevacizumab, and animal studies revealed increased accumulation of DOX at the tumor site and a significant delay of tumor growth in the combinational liposomal drug delivery group compared to free DOX, liposomal DOX, immunoliposomal DOX, and liposomal bevacizumab [71].…”
Section: Liposomes Combining In Vivo Longevity and Specific Target Rementioning
confidence: 99%